Roads to utopia : the walking stories of the Zohar - Greenstein, David, 1951- (Stanford, California : Stanford University Press, 2014)
This is the first in-depth study of the 'walking motif' of the Zohar. The Zohar is unique among Jewish mystical texts in continuously introducing and punctuating its teachings with references to its mystical adepts' 'walking along the road'. By carefully cataloguing and analyzing the use of the walking motif, this study seeks to show that it expresses a concern of the Zohar that is surprising for a mystical text: to recognise the steady, if problematic, presence of a non-mystical dimension to reality, the domain of the mundane.
Studying the Zohar : a unique book and a unique motif -- Spatiality and the Zohar : places, spaces, and movement in and through them -- The dregs of tar -- Walking with God -- The spatial orientation of the Zohar -- The body wishes to walk -- The broad dissemination of Torah : "the Torah is not the heritage of only one place" -- Zoharic geographics -- Conclusion : the quotidian utopia of the Zohar.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 630, 650
Keywords: Zohar; Zohar; Cabala; Mysticism -- Judaism; Walking in literature; Jewish literature -- Themes, motives; RELIGION -- Judaism -- General; Cabala; Mysticism -- Judaism; Walking in literature; Cabala; Jewish literature -- Themes, motives; Mysticism -- Judaism; Walking in literature; Zohar; Electronic books